Cytotoxic and genotoxic properties of artathomsonine, a new oxoberberine alkaloid from Artabotrys thomsonii (annonaceae). Issue 11 (2nd June 2022) - Nguemdjo Chimeze, Valery Wilfried; Bankoglu, Ezgi Eyluel; Zühlke, Sebastian; Fannang, Véronique Simone; Eckelmann, Dennis; Chi Shirri, Jovita; Djuidje, Ernestine Nicaise; Djama, Céline Mbazoa; Stopper, Helga; Wandji, Jean
Abstract: A phytochemical investigation of the liana of Artabotrys thomsonii led to the isolation of a new oxoberberine alkaloid, 2, 10-dihydroxy-3, 9-dimethoxy-8-oxo-protoberberine (7 ), along with six known compounds. Their chemical structures were elucidated by 1 D and 2 D NMR spectroscopic methods and HRESI-MS n data analysis. Compounds 4 and 7 were selected for further in vitro investigations. In accordance with expectations from their chemical structures, compounds 7 and 4 showed a clear antioxidant activity in a cell-free assay, with compound 7 being 7-fold more active than 4 . Cytotoxicity, cytostatic and genotoxic effects only occurred at high micromolar concentrations of 50 µM or more. Compound 7 was slightly less effective than compound 4 . A low micromolar concentration of 10 µM did not cause any damaging cellular effects but showed potential for a protection against the micronucleus-inducing effect of reactive oxygen species hydrogen peroxide, although not to a significant extent. Graphical Abstract: UF0001